Characterization and Identification of Phytochemical Compounds Soursop Leaf Extract (Annona muricata L.) - Amrullah, Kammal Nizam Amrullah; Ma’rifah, Shofia Jannatul; Azizah, Nur; Jamilah, Zahrotul; Safitri, Dewi Astriana; Bawani, Elen Ayu; Ramadhan, Majida; Hayati, Ari; Nafisa; Mahyantika, Seftya Putri (JSMARTech, 2025)
Soursop leaves (Annona muricata L.) have long been used in traditional medicine in Indonesia to treat various diseases. This study aimed to characterize and identify phytochemical compounds present in soursop leaf extract. The analysis was carried out using UV-Visible spectrophotometric, FT-IR spectroscopy, and phytochemical screening to identify the presence of bioactive compounds such as alkaloids, flavonoids, and tannins. UV-Visible spectrophotometric analysis showed a characteristic of the isoflavone spectrum with two absorption peaks of 310-330 nm. FT-IR revealed strong absorption at 3380 cm-1 (O-H group), 1737 cm-¹ (C=O group), and 718 cm-1 (C-H alkene group), along with moderate absorption at 2922 cm-1 and 2852 cm-2 (C-H alkane group) and 1650 cm-1 (C=C alkene group). The total flavonoid content of the extract was 89.201 mg/g at 1000 ppm and 87.220 mg/g at 500 ppm. These findings indicate that soursop leaves are rich in flavonoids and other bioactive compounds with potential medicinal value. Keywords: Soursop leaves, UV-Visible, FT-IR, phytochemical screening, total flavonoids